Carbon quantum dots-TiO2 nanocomposite as an efficient photocatalyst for the photodegradation of aromatic ring-containing mixed VOCs: An experimental and DFT studies of adsorption and electronic structure of the interface - Mahmood, Asad; Shi, Gansheng; Wang, Zhuang; Rao, Zepeng; Xiao, Wang; Xie, Xiaofeng; Sun, Jing (Journal of hazardous materials, 2021)
[Display omitted] •CQDs significantly improved the photocatalytic activity of TiO2 NPs.•The photodegradation of mixed VOCs on CQDs/TiO2 nanocomposite was examined.•Adsorption mechanism of mixed VOCs on TiO2 was rationalized using DFT.•The CQDs/TiO2 interface was studied using DFT. In this work, we have developed and optimized TiO2 nanoparticles decorated with carbon quantum dots to examine its potential use in the photocatalytic oxidation of aromatic ring containing gas-phase mixed volatile organic compounds, e.g., benzene, toluene, and p-xylene. Carbon quantum dots decorated TiO2 demonstrated good photodegradation efficiency in contrast to pure TiO2 under UV–vis light illumination. For example, with 0.5 wt% carbon quantum dots decorated on TiO2, 64 % of the mixed volatile organic compounds were photodegraded, while pure TiO2 only exhibited 44 % of the photodegradation efficiency. Also, the carbon quantum dots (0.5 wt%)/TiO2 nanocomposite demonstrated considerable photocatalytic activity within the visible region. On the other hand, pure TiO2 remained inactive within the visible region. The density functional theory study of the carbon quantum dots/TiO2 interface revealed that C 2p states of carbon quantum dots incorporated new energy states around the Fermi level near the lowest conduction band. This might be accountable for the improved charge separation process and better conductivity of the photogenerated electrons. The improved photocatalytic performance of the carbon quantum dots/TiO2 nanocomposites can be attributed to good light harvesting within the UV–vis region, charge separation, and adsorption capability.